MORFOTEKTONIK DAS CITARIK HULU KAITAN DENGAN TATA GUNA LAHAN, DI WILAYAH CICALENGKA, KAB. BANDUNG - Mochamad Aufar Muttaqin; Murni Sulastri; Nana Sulaksana; P Paramarta Raditya Rendra (Journal of Geoscience Engineering & Energy (JOGEE), 2022)
The Upper Citarik sub-watershed area is part of the Citarum watershed. Most of the surrounding land is used as agricultural areas, gardens, rice fields, forests, and settlements. With most of the people working as farmers, it causes land degradation due to agricultural extensification. Because the Cicalengka area is estimated to be the final part of the Lembang Fault, and an area that has experiencing changes of land use, this study aims to examine the relationship between the morphotectonic aspects of the Upper Citarik watershed and land use around the Citarik River. The approach used to identify morphotectonic influences in the research area is the analysis of the ridge lineament pattern as well as geomorphic analysis in the form of bifurcation ratio (Rb), drainage density (Dd), mountain front sinousity (Smf), and valley floor width to height ratio (Vf). The dominant pattern of ridge lineaments in the study area is northeast-southwest, resulting in mountains oriented northwest-southeast. The average Rb value is 3.64, Dd ranges from 0.25-10, Vf with an average of 0.62, and the Smf value ranges from 1.11-1.64 in the north and 1.3-2.39 in the south. It can be interpreted that the tectonic activity of the surrounding area is classified as moderately active tectonic, and there are differences in tectonic classes between the northern and southern parts.